Emotional response bias, autistic traits and paranormal beliefs in patients with OCD - Ayesha Ashraf; Rabia Iftikhar (Journal of the Pakistan Medical Association, 2021)
Objective: To find the relationship involving autistic traits, paranormal beliefs and emotional response bias in obsessive compulsive disorder patients. Method: The cross-sectional quasi-experimental study was conducted from November 2017 to November 2018 at the Government College University, Lahore, Pakistan, and comprised patients with obsessive compulsive disorder and healthy controls from the general population aged 20-40 years. Data was collected using the self-reporting Autism Spectrum Quotient, the Revised Paranormal Belief Scale, the Emotional Recognition Task and the Obsessive Compulsive Disorder symptom checklist. Data was analysed using SPSS 20. Results: Of the 140 participants, there were 70(50%) patients and as many controls. Overall, there were 72(52%) males and 68(48%) females. High level of autistic traits (p<0.001) and paranormal beliefs (p<0.001) had a significant impact on obsessive compulsive disorder. Impairments in recognition of emotions were related to the presence of high autistic traits and obsessive compulsive symptoms in the patients group (p<0.05). Emotion of disgust (p<0.001) was significantly impaired in the patients, while the differences were not significant in terms of emotions of happiness and surprise (p>0.05). Conclusion: Autistic traits, paranormal beliefs and emotional response bias were found to have a significant relationship in obsessive compulsive disorder patients. Continuous....